Hydroxytyrosol and Olive-Derived Hydroxytyrosol-Rich Products for Skin Health and Prevention of Skin Ageing: Current Evidence and Future Perspectives - Adriana Albini; Danilo Morelli; Cecilia Bender; Paola Corradino (Antioxidants, 2026)
Skin health is increasingly recognised as a key determinant of overall well-being, and its decline is driven by multiple interconnected biological processes. Hydroxytyrosol (HT), an olive polyphenol, exhibits pleiotropic biological activities and has a potential role in supporting skin homeostasis. This narrative review critically evaluates the evidence on oral HT and HT-rich olive-derived nutraceuticals for skin health and healthy ageing with a focus on oxidative damage, inflammation, photoprotection, extracellular matrix (ECM) preservation, wound healing, and skin pigmentation conditions. HT exhibits high oral bioavailability and modulates antioxidant defences, inflammatory signalling, autophagy, apoptosis, and metabolic homeostasis. Preclinical studies consistently show protective effects against oxidative stress, ECM degradation, cellular senescence, photoageing, impaired wound healing, and ultraviolet-induced skin damage. Experimental evidence also indicates antiproliferative and pro-apoptotic effects in melanoma models through modulation of oncogenic signalling pathways, suggesting a potential role in skin cancer prevention. In vivo, oral HT administration improves glycative skin ageing, psoriasis, intestinal barrier integrity, and systemic inflammation. Clinical evidence supports systemic antioxidant and cardiometabolic benefits of purified HT and HT-rich formulations, while dermatological evidence remains preliminary for psoriasis, melasma, and wound healing. Overall, HT shows promise, but randomised controlled trials with validated dermatological endpoints are needed to confirm its clinical efficacy.